KOHERENSI ANTARKALIMAT PADA PARAGRAF DALAM WACANA ILMIAH BAHASA JAWA (Coherence Between Sentences on Paragraph in Javanese Language Scientific Discourse) - NFN Sumadi (Kantor Bahasa Sulawesi Tenggara, 2017)
This research discusses about various kinds of coherence between sentences in Javanese language scientific discourse. Qualitative descriptive method is used in this research due to objectives of the research that is to provide kinds of coherence between sentences in the Javanese language scientific discourse. The sentence coherence in Javanese scientific discourse paragraph can be differentiated as (1) causality, (2) analysis (partial analysis, functional analysis, process analysis), (3) opposition, (4) validation, (5) continuity, (6) addition, (7) sequence, and (8) explanation. Any kind of coherence can be signified with cohesion, which is not only originated from the Javanese language, but also can be absorbed from Indonesia language or not signified.